1995
DOI: 10.1046/j.1471-4159.1995.65041569.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Modulation of Membrane‐Associated Protein Kinase C Activity by an Endogenous Inhibitor Plays a Role in N1E‐115 Murine Neuroblastoma Cell Differentiation

Abstract: Murine neuroblastoma cells, N1E‐115, were induced to differentiate into neuron‐like cells by serum deprivation for 18 h. As previous studies have shown that the suppression of protein kinase C (PKC) activity by selective inhibitors or neutralizing antibodies induces neuroblastoma cells to differentiate, we tested the hypothesis that serum deprivation may cause a rapid loss in membrane PKC activity that occurs well before the morphological changes that are characteristic of cell differentiation. A significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Current studies are addressing the possibility that reversible inactivation of PKC following glutamate receptor hyperactivation in cells 16 DIV results from the suppression of enzyme activity by a membrane-bound PKC inhibitor that may regulate PKC or perhaps specific PKC isoforms, located proximally to ionotropic glutamate receptors. We have recently demonstrated that such a membrane-bound protein inhibitor of PKC exists in NIE-l IS neuroblastoma cells and that this protein appears responsib!e for the loss of PKC activity needed for the differentiation of these cells into neurons under serum-free conditions (Chakravarthy et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies are addressing the possibility that reversible inactivation of PKC following glutamate receptor hyperactivation in cells 16 DIV results from the suppression of enzyme activity by a membrane-bound PKC inhibitor that may regulate PKC or perhaps specific PKC isoforms, located proximally to ionotropic glutamate receptors. We have recently demonstrated that such a membrane-bound protein inhibitor of PKC exists in NIE-l IS neuroblastoma cells and that this protein appears responsib!e for the loss of PKC activity needed for the differentiation of these cells into neurons under serum-free conditions (Chakravarthy et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that this peptide targets AβO aggregates when microinjected into the hippocampi of living double-transgenic AD mice harboring PSEN1dE9 and APP SWE transgenes [ 73 ] and also ex vivo in brain sections of both transgenic mice and postmortem human AD patients. Interestingly, ABP, which can also inhibit membrane-associated PKC activity) [ 75 , 76 ] is actually the 1276–1314 region of the human PCM1 described above.…”
Section: How Might Ad Be Treated?mentioning
confidence: 99%
“…Li et al [71] have also shown that an antibody that selectively targets the N-tails, but not one that targets the C-termini, of soluble AβOs rescues the ability of the hippocampal CA1 cells to establish LTP in AD mice. As discussed below, there may be other cellular proteins such as pericentriolar material-1 (PCM1) protein and myristoylated alanine-rich C kinase substrate (MARCKS) protein that can potentially bind AβOs through their cationic patches, 1276 KTFKTRKASAQASLASKDKTPKSKSKKRNSTQLKSRVKNI 1314 and 152 KKKKKRFSFKKSFKLSGFSFK 172 , respectively, and mediate their effects [72][73][74][75][76].…”
Section: Aβ Oligomerslikely Ad-starters But Not the Terminatorsmentioning
confidence: 99%
“…The relatively low potency of VIP in stimulating cAMP accumulation suggests that VIP may be interacting with the type I PACAP receptors. Because NIE-l 15 cells have frequently been used for the study of molecular mechanisms of neuronal differentiation (Richelson, 1973;de Laat and van der Saag, 1982;Chakravarthy et al, 1995: Kranenburg et al, 1995, to understand the trophic action of PACAP, it is important to establish the effect of PACAP on neurite outgrowth and the signaling mechanisms activated by PACAP/VIP in these cells. Therel'ore, the objectives of this study were (a) to characterize the signaling mechanisms activated by the three peptides, PACAP38, PACAP27, and VIP.…”
Section: -Pacap27mentioning
confidence: 99%
“…Furthermore, two other signaling mechanisms of importance to neuronal differentiation, elevation of [Ca2 jãnd PKC (Reboulleau, 1986;Herrick-Davis et al, 1991), interact with the PACAP-stimulated cAMP response. Because NI E-115 cells are a useful model for the study of molecular mechanisms underlying neuronal differentiation (Richelson, 1973;Chakravarthy et al, 1995;Kranenburg et al, 1995), it would be important to identify the downstream mechanisms through which PACAP induces neurite outgrowth in NIE-1l5 cells.…”
Section: Volmentioning
confidence: 99%